Respiratory muscle training in older adults: review article - Vilaça,Adriano Florencio (2019)
OBJECTIVE: Respiratory muscle training has been considered one of the main strategies to alleviate sarcopenia in older adults. Therefore, the present study aimed to verify which respiratory muscle training protocols are most used in this population and their main benefits described in the literature. METHODS: A literature search was performed in the electronic databases PubMed, Latin American and Caribbean Health Sciences Literature (LILACS) and Scientific Electronic Library Online (SciELO). For this, we used the terms: respiratory muscle training, older adults, and muscle weakness. A total of 80 articles were studied, of which only 8 met the inclusion criteria of this study, whose methodology, variables studied, and outcome were analyzed. RESULTS: Among the 8 articles analyzed, we can observe an important diversity of the studied protocols; and all articles showed the most varied gains possible with respiratory muscle training. CONCLUSION: The protocols used in the various studies depend directly on the objective to be achieved with respiratory muscle training; and the main outcomes were improvements in strength, lung function, physical fitness level, quality of life, inflammatory markers and glucose intake.